Effect of Plant Bioactive Compounds Supplemented in Transition Dairy Cows on the Metabolic and Inflammatory Status - Dana Kumprechtová; Thibaut Chabrillat; Simon Guillaume; Sylvain Kerros; Romana Kadek; Eva Indrová; Josef Illek (Molecules, 2022)
(1) Background: This study evaluated the effects of a plant bioactive (Phyto Ax’Cell, Phytosynthese, Mozac, France) on the inflammatory status and health of dairy cows during calving. (2) Methods: 46 Holstein crossbred cows were randomized into a control group (CON, n = 23) and the Phyto Ax’Cell group (PAC, n = 23). PAC received Phyto Ax’Cell at 25 g/cow/day, from 15 days prepartum to 7 days postpartum. Blood analyses were performed weekly from D-7 to D14 to evaluate the energy metabolism and inflammatory status; rectal temperature was measured daily within 14 days from calving day (D0). (3) Results: PAC showed lower serum haptoglobin at D7 (0.55 vs. 0.79 mg/mL; p < 0.05) and D14 (0.44 vs. 0.66 mg/mL; p < 0.05). CON had a higher number of circulating white blood cells and granulocytes on D7 (p < 0.05). Fewer cows from PAC showed hyperthermia (≥39 °C) during the first 2 weeks postpartum (−7%, p < 0.05). Energy metabolism, which was represented by the NEFA/cholesterol ratio, improved (0.21 vs. 0.36 at D0, p < 0.1; 0.19 and 0.15 vs. 0.36 and 0.32, respectively, at D+7 and D+14, p < 0.05) under the plant bioactive supplementation. (4) Conclusions: The results suggest that the anti-inflammatory plant bioactive compound with Brazilian green propolis administered during calving had a beneficial effect on the energy and inflammatory status of dairy cows.